Growth, Carcass and Feed Consumption of Native Chicken Given Feed Containing Fermented Cocoa Husk Flour - Luh Suariani; I Nyoman Kaca; I Gusti Agus Maha Putra Sanjaya; Joshua Novertis Bobo; Agung Gumelar Jode (PT FORMOSA CENDEKIA GLOBAL, 2024)
The improvement of the performance of native chicken needs to be balanced with the improvement of its ration. The ingredients of the ration used do not need to be expensive, but good quality, easy to obtain, and available throughout the year. One of the feed ingredients that is widely available and is waste is Cocoa skin. Fermented Cocoa skin has a nutritional content of 2.63%, crude fat 20.14%, crude fiber, 10.39% crude protein, calcium 7.18%, and phosphorus 2.06%. Cocoa skin, in addition to its high crude fiber, also contains antinutrients in the form of tannins. Therefore, fermentation is necessary. The design used in this study was a Completely Randomized Design (CRD) with 5 (five) treatments and 3 (three) replications. The variables observed were Growth, ration consumption, protein consumption, Whole carcasses harvested when the chickens were 10 weeks old. The provision of fermented Cocoa skin up to 10% did not give a significant effect (P>0.05) on weight gain, final body weight, and whole carcass weight of native chicken aged 3-10 weeks. However, the provision of fermented Cocoa skin flour gave a significant effect on ration consumption, protein consumption, and energy consumption in native chicken aged 3-10 weeks. The best provision was obtained in the treatment of provision of fermented Cocoa skin flour as much as 5%